Implementation of Marriage Contracts for the Deaf: A Case Study in West Kotawaringin Regency, Central Kalimantan - Ansaruddin; Abdul Helim; Abdul Khair (Academia Publication, 2024)
This research is an in-depth study of deaf marriages in West Kotawaringin Regency, focusing on the prevalence and characteristics of their marriages. The research methods include case studies, surveys, interviews, observations, and document analysis. The results show that the entire deaf population in the region is married, with age, education, and socio-economic status significantly influencing the decision to marry. Deaf marriages are characterized by the use of sign language as the primary medium of Communication and face challenges such as social stigma and limited access to marriage services. The findings of this study highlight the importance of collaborative interventions between the government, relevant agencies, and communities to improve support for deaf individuals in living their married lives. Recommendations from this study can serve as the basis for more inclusive policies to support the welfare and rights of deaf couples in marriage.